THE INFLUENCE OF THE HEAD PHARMACIST’S LEADERSHIP STYLE AND ORGANIZATIONAL SUPPORT ON PHARMACY TEAM PERFORMANCE AND ITS IMPACT ON THE SUCCESS OF DRUG THERAPY IN MELINDA HOSPITALS - Fransisca Intan Marulita; Haddan Dongoran; Rukhiyat Syahidin; Ayu Laili Rahmiyati; Farida Yuliaty (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of the head pharmacist’s leadership style and organizational support on the success of drug therapy through the performance of the pharmacy team in a hospital setting. It is motivated by the importance of effective leadership and organizational support in improving team performance and patient therapy outcomes. This study employed a quantitative method with descriptive and verificative approaches. The population consisted of pharmacy personnel, with total sampling used to obtain 48 respondents. Data were analyzed using multiple linear regression and mediation analysis with the PROCESS Macro (Hayes). Statistical tests included validity, reliability, t-test, F-test, and coefficient of determination using SPSS. The results showed that the head pharmacist’s leadership style and organizational support significantly affect pharmacy team performance. Pharmacy team performance also has a significant effect on the success of drug therapy. In addition, leadership style and organizational support have a direct effect on therapy success. Mediation analysis indicated that pharmacy team performance acts as a mediating variable in the relationship between leadership style, organizational support, and drug therapy success. In conclusion, drug therapy success is influenced both directly and indirectly through improved pharmacy team performance. Therefore, hospitals should strengthen leadership practices and organizational support